Campaña de posicionamiento de la revista institucional de la Universidad de Piura: Amigos - Cerna Laguna, Daniela Nataly (2019)
The aim of this project is to chronicle the planning and execution of a 3-month brand awareness campaign made for "Amigos", the institutional magazine of the University of Piura. Through a strategic communication plan that brought together content marketing, digital marketing, and ‘below the line’ advertising actions, it was sought to position the "Amigos" brand among the students of Campus Lima of the University of Piura. In the following chapters, the campaign is described in detail; from the origins and history of the magazine to the definition of the brand concept, the concrete actions taken for its promotion and positioning, as well as the reviewing of their results.